Childhood Socialization in Post-Conflict Societies: Intergenerational Transmission of Trauma and Its Impact on Learning Behavior in Nepal - Kamal Singh Kunwar (PT. Global Research Collaboration, 2026)
Armed conflict can produce enduring psychosocial consequences that extend across generations and influence children’s educational development. This study examined the relationship between intergenerational trauma and learning behavior in post-conflict Nepal, with particular attention to the mediating roles of childhood socialization, including parenting style, emotional climate, and social trust. A convergent parallel mixed-methods design was employed. Quantitative data were collected from 400 students aged 10–16 years in conflict-affected districts and analyzed using confirmatory factor analysis and structural equation modeling. Qualitative data were obtained through semi-structured interviews with 25 students, parents, and teachers and analyzed thematically. The structural model demonstrated an acceptable fit to the data. Intergenerational trauma was negatively associated with emotional climate, parenting style, and social trust, while all three socialization dimensions were positively associated with students’ attention, motivation, and academic engagement. Emotional climate emerged as the strongest mediating pathway, followed by parenting style and social trust. Although intergenerational trauma retained a significant direct negative association with learning behavior, the combined indirect effect through childhood socialization was stronger. The qualitative findings supported these statistical relationships by revealing persistent household tension, inconsistent parental support, reduced trust, and lower classroom participation among students from trauma-affected families. These findings indicate that the educational consequences of intergenerational trauma are largely transmitted through the relational and emotional environments in which children develop. The study highlights the need for trauma-informed educational policies, teacher preparation, family-based support, and school-linked psychosocial services in post-conflict Nepal.